2013
DOI: 10.3892/br.2013.52
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress mediates nitric oxide-induced chondrocyte apoptosis

Abstract: Nitric oxide (NO) is one of the most important mediators of chondrocyte apoptosis, which is a notable feature of cartilage degeneration. While apoptosis of chondrocytes is induced by p53, NO can also induce endoplasmic reticulum (ER) stress, which may be involved in the process of NO-induced chondrocyte apoptosis. The aims of this study were to determine whether NO-induced ER stress (ERS) leads to apoptosis of chondrocytes and to investigate the temporal relationship between the expression of C/EBP-homologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Therefore, excess NO could directly disturb ER function and activate ER stress, which could mediate PUMA-induced apoptosis in PHG as described in our previous and current studies [11]. Several reports have also revealed that the ER stress pathway involving C/EBP homologous protein (CHOP) was important in NO-induced apoptosis of some cell types, and that blockage of NO production could alleviate apoptosis [16][17][18]. While, the role played by TNF-α in PHG was via regulation of NO production, which has been also shown to activate ER stress.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Therefore, excess NO could directly disturb ER function and activate ER stress, which could mediate PUMA-induced apoptosis in PHG as described in our previous and current studies [11]. Several reports have also revealed that the ER stress pathway involving C/EBP homologous protein (CHOP) was important in NO-induced apoptosis of some cell types, and that blockage of NO production could alleviate apoptosis [16][17][18]. While, the role played by TNF-α in PHG was via regulation of NO production, which has been also shown to activate ER stress.…”
Section: Discussionmentioning
confidence: 68%
“…The ER stress/PUMA pro-apoptotic signaling network plays a pivotal role in cell death in a variety of tissues in response to hypoxia, ischemia and noxious drugs [12][13][14], of which nitric oxide (NO), an important mediator of physiological and pathological processes, contributes to the ER stress reaction and apoptosis of cells in various diseases [15][16][17][18]. NO is produced by NO synthase (NOS), with three main isoforms of NOS having been identified: neuronal NOS (nNOS), endothelial NOS (eNOS), and inducible NOS (iNOS) [19].…”
Section: Introductionmentioning
confidence: 99%
“…The NO produced was measured on a microplate reader at 540 nm. The changes evoked in NO levels were determined by comparison with data points obtained in the absence of CMA3 (25).…”
Section: Neutralization Of Lpsmentioning
confidence: 99%
“…Yet another TF that was strongly upregulated by NO in juvenile HSCs was Chop1 . It is a basic leucine-zipper protein induced by a variety of stimuli, including NO [52], that evokes cellular stress responses. On the other hand, deletion of its homologous TF, C/EBP, has been shown to affect self-renewal of HSCs [31].…”
Section: Discussionmentioning
confidence: 99%